2017
DOI: 10.1159/000474959
|View full text |Cite
|
Sign up to set email alerts
|

Use of Phosphorus Binders among Non-Dialysis Chronic Kidney Disease Patients and Mortality Outcomes

Abstract: Background: Whether the benefits of phosphorus binders extend to those without end stage renal disease is uncertain. Among a large diverse non-dialysis chronic kidney disease (CKD) population with hyperphosphatemia, we sought to evaluate phosphorus binder use and compare mortality risk between patients prescribed and not prescribed binders. Methods: A retrospective cohort study within an integrated health system (January 1, 1998 - December 31, 2012) among CKD patients (age ≥18) was performed. Non-dialysis CKD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…In a meta-analysis, patients who had CKD stages 3‒5d and were using sevelamer had lower all-cause mortality than those who were using calcium-based binders to treat hyperphosphatemia [ 21 ]. In patients with CKD, a retrospective study found that the use of phosphate binders was associated with a lower risk of mortality [ 22 ]. On the other hand, iron-deficiency anemia is a major problem in ESKD [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a meta-analysis, patients who had CKD stages 3‒5d and were using sevelamer had lower all-cause mortality than those who were using calcium-based binders to treat hyperphosphatemia [ 21 ]. In patients with CKD, a retrospective study found that the use of phosphate binders was associated with a lower risk of mortality [ 22 ]. On the other hand, iron-deficiency anemia is a major problem in ESKD [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…The hypothesis that elevations in serum phosphorus level are deleterious is rooted in observations showing associations between higher serum phosphorus levels and adverse clinical outcomes in patients with all levels of kidney function. 10 , 11 , 12 , 13 , 14 A causal role of phosphorus in these associations has been implied based on experimental data suggesting that phosphorus can be instrumental in inducing pathologic changes in the vasculature, 16 , 17 and based on observational studies showing associations between the administration of phosphate binders and better clinical outcomes in patients with NDD-CKD 19 , 20 and end-stage renal disease. 18 However, no clinical trials were ever designed to prove that lowering serum phosphorus (vs. not lowering it) can improve mortality or cardiovascular event rates, and a network meta-analysis of available clinical trial data from studies assessing other end points also suggested no effects on mortality compared with placebo.…”
Section: Discussionmentioning
confidence: 99%
“…In spite of compelling observational data and plausible pathophysiologic mechanisms to explain the association of abnormal phosphorus metabolism with adverse outcomes, 16 , 17 the benefit of phosphorus-lowering therapy remains questionable. The administration of phosphorus binders to dialysis patients 18 and to patients with NDD-CKD 19 , 20 was associated with lower mortality in observational studies, but clinical trials aimed at phosphorus lowering using various strategies showed inconsistent outcomes on biochemical or vascular end points. 21 , 22 , 23 , 24 , 25 In a randomized controlled clinical trial (RCT) examining the effects of sevelamer hydrochloride versus calcium carbonate versus dietary phosphate restriction on coronary calcification in 90 patients with NDD-CKD, 21 the highest progression of coronary calcification was seen in the group treated with dietary restriction alone, and the lowest progression in the group administered sevelamer hydrochloride.…”
mentioning
confidence: 99%
“…13 Hyperphosphatemia has been identified as an independent risk factor for death in patients with end-stage renal disease, 14 but that relationship is less clear in patients with chronic kidney disease. A study in patients with chronic kidney disease and not on dialysis found a lower mortality rate in those who were prescribed phosphorus binders, 15 but the study was criticized for limitations in its design.…”
Section: ■ Hyperphosphatemia May Lead To Vascular Calcificationmentioning
confidence: 99%